Streptococcal Endo-β-N-Acetylglucosaminidase Suppresses Antibody-Mediated Inflammation In Vivo - Nandakumar, Kutty Selva; Collin, Mattias; Happonen, Kaisa E.; Lundström, Susanna L.; Croxford, Allyson M.; Xu, Bingze; Zubarev, Roman A.; Rowley, Merrill J.; Blom, Anna M.; Kjellman, Christian; Holmdahl, Rikard (Frontiers in Immunology, 2018)
Endo-β-N-acetylglucosaminidase (EndoS) is a family 18 glycosyl hydrolase secreted by Streptococcus pyogenes. Recombinant EndoS hydrolyzes the β-1,4-di-N-acetylchitobiose core of the N-linked complex type glycan on the asparagine 297 of the -chains of IgG. Here we report that EndoS and glycans hydrolyzed by EndoS induced suppression of local immune complex (IC)-mediated arthritis. A small amount (1 µg given i.v. to a mouse) of EndoS was sufficient to inhibit IgG-mediated arthritis in mice. The presence of EndoS disturbed larger IC lattice formation both in vitro and in vivo, as visualized with anti-C3b staining. Neither complement binding in vitro nor antigen-antibody binding per se were affected. Thus, EndoS could potentially be used for treating patients with immune complex mediated pathology.